Streptococcus agalactiae INFECTION ON TILAPIA (Oreochromis niloticus) IN CIRATA RESERVOIR, WEST JAVA - Angela Mariana Lusiastuti; Lila Gardenia; Tatik Mufidah; Yani Aryati (Indonesian Aquaculture Journal, 2009)
Streptococcosis is one of bacterial diseases in the culture of Tilapia, Oreochromis niloticus and has caused significant economic losses. Streptococcus iniae, is known as pathogen to marine and freshwater fishes whereas Streptococcus agalactiae is known as pathogen to Tilapia. The isolation and characterization of four isolates of S. agalactiae, were described from an infected Tilapia from Cirata Reservoir, West Java, in July 2008. Conventional and rapid identification systems were used to determine isolates of S. agalactiae from brain and kidney tissues. In this paper, we have characterized S. agalactiae and this was the first isolation of this bacteria from fish. The isolates were gram positive, catalase-negative, oxidase-negative,  haemolytic cocci colonies on blood agar. All of the of isolates were biochemically characterized with the API 20 Strep System (bioMerieux). Bacterial chromosomal DNA used in PCR assay was extracted by heating method. The forward primer is Sdi 61: 5’-AGGAAACCTGCCATTTGCG-3’ and the reverse primer is Sdi 252: 5’-CAATCTATTTCTAGATCGTGG-3’ with gene target 16S intergenic spacer and it has 192 bp in length. These primers were designed by Alpha DNA (Montreal, Quebec). The biochemical patterns of four isolates were rather different although almost all traits were similar with the exception of pyroglutamic acid (pyra) and L-arginin (ADH), for which we observed negative and positive reaction in this study. Therefore, some of the biochemical characteristics of the four isolates did not fit 100% with the typical patterns of S. agalactiae. However, the PCR result showed that this PCR assay is an effective tool for rapid and specific detection of S. agalactiae, the main pathogens involved in warm-water streptococcosis, obtained from pure culture of naturally infected fish. Therefore, it could be a useful alternative for culture-based routine diagnosis of warm-water streptococcal infections in fish.